2017
DOI: 10.3390/molecules22050701
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Mediated by Costus afer Leaf Extract: Synthesis, Antibacterial, Antioxidant and Electrochemical Properties

Abstract: Synthesis of metallic and semiconductor nanoparticles through physical and chemical routes has been extensively reported. However, green synthesized metal nanoparticles are currently in the limelight due to the simplicity, cost-effectiveness and eco-friendliness of their synthesis. This study explored the use of aqueous leaf extract of Costus afer in the synthesis of silver nanoparticles (CA-AgNPs). The optical and structural properties of the resulting silver nanoparticles were studied using UV-visible spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 71 publications
5
46
0
Order By: Relevance
“…Spherical AgNPs synthesized byElemike et al (2017c) using leaf extract of Talinum triangulare averaged 13.86 nm in size and scavenged DPPH better than the extract, and with comparable performance with ascorbic acid. Costus afer extract-mediated AgNPs reported byElemike et al (2017d) also scavenged DPPH at different concentrations. The nanoparticles scavenged DPPH better than the leaf extract, while it had comparable action with ascorbic acid.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Spherical AgNPs synthesized byElemike et al (2017c) using leaf extract of Talinum triangulare averaged 13.86 nm in size and scavenged DPPH better than the extract, and with comparable performance with ascorbic acid. Costus afer extract-mediated AgNPs reported byElemike et al (2017d) also scavenged DPPH at different concentrations. The nanoparticles scavenged DPPH better than the leaf extract, while it had comparable action with ascorbic acid.…”
mentioning
confidence: 87%
“…Results from cyclic voltammetry experiments revealed that AgNPs-functionalized MWCNT had the best conductivity, which can be deployed for electrocatalysis. Also, CA-AgNPs phytosynthesized by the aqueous extract of C. afer described previously was studied for electrochemical properties (Elemike et al, 2017d). The CA-AgNPs/ MWCNT-modified electrode transfers charge well; a property that can be explored as a sensor in assaying biological and environmental samples.…”
Section: Antioxidant Catalytic and Sensing Activitiesmentioning
confidence: 99%
“…In presence of DPPH, copper oxide nanomaterials have a capacity to transfer an electron density towards the free radical located on nitrogen atom. [57][58][59][60]…”
Section: Free Radical Scavenging Activitymentioning
confidence: 99%
“…Consequently, biomolecules of plant extracts are presently being investigated universally to control dimension, shape and consistency of the nanoparticles. Recently, biosynthesis of Ag NPs has been conducted with Eucalyptus chapmaniana , Thymbra spicata , Arbutus unedo , Artemisia nilagirica , Sesbania grandiflora , Allium sativum , Datura metel , Malva parviflora , Cinnamon zeylanicum , Costus afer , Lippia citriodora , Gliricidia sepium , green tea, Tephrosia purpurea , oak fruit bark, Ocimum tenuiflorum , Manilkara zapota (L.) and Stachys lavandulifolia . The extracts of several plant parts including leaves, roots, seeds, stems and fruits containing antioxidants have been investigated for the biosynthesis of pure Ag NPs.…”
Section: Introductionmentioning
confidence: 99%